SOCIAL RESPONSE OF KALIPEPE VILLAGE COMMUNITY IN YOSOWILANGUN SUB-DISTRICT IN THE IMPLEMENTATION OF PMK NUMBER 222/PMK.07/2020 ON VILLAGE FUND MANAGEMENT - Saefudin Zuhri; Supranoto Supranoto; Ika Sisbintari (DIA: Jurnal Administrasi Publik, 2024)
The present study is to identify and analyze the social dynamics of the Kalipepe Village community in Yosowilangun Subdistrict in the implementation of PMK Number 222 / PMK.07 / 2020 regarding Village Fund Management. This study employs a descriptive research method with a qualitative approach. Based on the results, it was found that the community's social response did not meet one of the eight dimensions or criteria as seen from Lassawell's grand theory. These dimensions include sender, encoding, message, media, decoding, response, feedback, and noise. Specifically, the response dimension was found to be either inappropriate or not fully met. To enhance the community's social response, it is essential for the village government to prioritize transparency in both communication and mechanisms in the field. This approach will help prevent potential issues that could undermine equity and justice.